Impaired Retinal Vasoreactivity: An Early Marker of Stroke Risk in Diabetes. Issue 1 (28th November 2016) - Bettermann, Kerstin; Slocomb, Julia; Shivkumar, Vikram; Quillen, David; Gardner, Thomas W.; Lott, Mary E.
ABSTRACT: Diabetes is a common cause of small vessel disease leading to stroke and vascular dementia. While the function and structure of large cerebral vessels can be easily studied, the brain's microvasculature remains difficult to assess. Previous studies have demonstrated that structural changes in the retinal vessel architecture predict stroke risk, but these changes occur at late disease stages. Our goal was to examine whether retinal vascular status can predict cerebral small vessel dysfunction during early stages of diabetes. Retinal vasoreactivity and cerebral vascular function were measured in 78 subjects (19 healthy controls, 22 subjects with prediabetes, and 37 with type‐2 diabetes) using a new noninvasive retinal imaging device (Dynamic Vessel Analyzer) and transcranial Doppler studies, respectively. Cerebral blood vessel responsiveness worsened with disease progression of diabetes. Similarly, retinal vascular reactivity was significantly attenuated in subjects with prediabetes and diabetes compared to healthy controls. Subjects with prediabetes and diabetes with impaired cerebral vasoreactivity showed mainly attenuation of the retinal venous flicker response. This is the first study to explore the relationship between retinal and cerebral vascular function in diabetes. Impairment of venous retinal responsiveness may be one of the earliest markers of vascular dysfunction in diabetes possibly indicating subsequent risk of stroke and vascular dementia.